Effect of Micro-Arc Pre-Oxidation on Wear and Corrosion Resistance of Low-Temperature Plasma Nitrided Layer on Ti6Al4V Titanium Alloy - YANG Jiale, XU Lixin, LI Dongshan, PENG Zhenjun, ZHANG Guangan, JIANG Changjun (Cailiao Baohu)
In order to improve the wear resistance and corrosion resistance of Ti6Al4V (TC4) titanium alloy, surface modification of TC4 titanium alloy was carried out using micro-arc oxidation (MAO),low-temperature plasma nitriding (PN) and plasma nitriding after micro-arc oxidation.Subsequently, the microscopic morphology, friction and corrosion resistance of the substate and the samples modified by three processes were studied by scanning electron microscopy, friction and wear testing machine and electrochemical workstation.Results showed that the micro-arc oxidation layer was mainly composed of rutile TiO2 and anatase TiO2 phases.The microhardness of the PN sample was (602±10)HV0.05, and the microhardness of the MAO-PN sample was (1 232±20) HV0.05, significantly higher than the microhardness of the TC4 titanium alloy substrate (352±5) HV0.05.In the atmospheric environment, compared to the TC4 titanium alloy substrate, the wear rates of MAO and MAO-PN samples decreased from 1.48×10－3 mm3/(N∙m) to 5.54×10－4 mm3/(N∙m) and 3.64×10－4 mm3/(N∙m), respectively.Under the lubrication of hydrochloric acid solution,compared with TC4 titanium alloy substrate,the friction coefficient of MAO and MAO-PN samples decreased from 0.35 to 0.25 and 0.18, respectively, and the wear rate decreased significantly from 3.62 × 10－4 mm3/(N∙m) to 3.50 × 10－6 mm3/(N∙m) and 1.57 × 10－6 mm3/(N∙m),respectively.This indicated that micro-arc pre-oxidation could greatly improve the wear resistance of plasma nitride layer.In hydrochloric acid solution, both MAO and MAO-PN samples exhibited abrasive wear mechanisms, while under atmospheric conditions and hydrochloric acid lubrication,TC4 titanium alloy and PN samples demonstrated adhesive wear mechanisms.Furthermore, the MAO-PN composite modified layer exhibited a lower corrosion current density (0.015 μA/cm2) and higher impedance value (9.90×105 Ω∙cm2) in hydrochloric acid solution, indicating that the micro-arc pre-oxidation process significantly enhanced the corrosion resistance of the plasma-nitrided titanium alloy layer.